Denúncia e dependência socioespacial: uma análise dos elementos da mobilização na cidade do Rio de Janeiro por meio do disque-denúncia, a partir de um modelo de regressão espacial - Ross, Steven Dutt (2007)
The objective of this dissertation is to analyze the socio-spatial distribution of the of denunciation rate. For this, it is studied association between the denunciations to Disque-Denúncia with the space position of the neighborhoods and the social characteristics in terms of the social context which can take to a greater or minor participation. The analysis will be centered in the relation between the socio-spatial variability of denunciations for 100.000 inhabitants and differences by the models of space regression and geographical representation highlighting the importance of the characteristics of the neighborhoods that generate the social context. The social configuration of a neighborhood, its space localization and its violence rate are the factors associates to the denunciation variability, which can modify its level. In relation to the space dependence of the neighborhoods, it is inferred that they are not independent. The denunciation rate of the neighborhoods is interdependent with close neighborhoods, because of the space externality. In relation to the social index of the neighborhoods, the result that we find is that the association of the denunciation rate with the percentage of elderly, the density and the average of studies of the neighborhoods exists, in other words, the levels of those are related with the levels of the denunciation rate.